Sensibility and specificity for pregnancy morbidity of anti-b2-glycoprotein I antibodies in antiphospholipid syndrome - S. Todesco (Reumatismo, 2011)
Objective: This study aimed to evaluate the sensitivity and specificity of the anti-b2-glycoprotein I antibodies for pregnancy morbidity in the antiphosoplipid syndrome (APS). Methods: 335 women were recruited and on the basis of their clinical features were subdivided into 2 groups homogenous for number and age. The first (study) group contained the women whose pregnancy complications satisfied the classification criteria for APS. The second (control) group was made up of women with pregnancy complications not included in the classification criteria for APS. Anti-b2-GPI, anticardiolipin antibodies (aCL) and lupus anticoagulants (LA) were determined in all of these women. Results: The only antiphospholipid antibodies occurring with a significant frequency (p=0,00) in the women with pregnancy criteria for APS were the IgG anti-b2-GPI and the IgG aCL present respectively in 23,92% and in 27,60% of the women. Its association was found to be significant (p=0,000). The distribution of the different levels of positivity of the IgG and IgM anti-b2 GPI in the patients of the study and control groups was not significantly different. The highest sensitivity for pregnancy complications was that of the IgG aCL and of the IgG anti-b2 GPI whose difference was not statistically significant. The comparison of the specificity of the IgG and IgM anti-b2 GPI with that of the IgG and IGM aCL was not statistically significant. Conclusions: The importance of determining the IgG anti-b2 GPI as part of routine laboratory testing of women with pregnancy complications typical of APS was confirmed. Together with IgG aCL these antibodies have proved to be the most sensitive and specific markers of pregnancy complications in APS.